INVESTIGATING READING STRATEGIES USED BY PROFICIENT READERS AND LOW READERS - Nur Auwalyah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Students' comprehension of a text relies much on the use of appropriate reading strategies during the activity. The use of strategies would improve students' comprehension of the text, which in turn helps them in their academic achievement at large. This study aimed to investigate the reading strategies used by proficient and low readers. The research design implemented in this study is descriptive qualitative. They were students of second grade English Department at University of Islam Malang. The result based on this research, it can be concluded that low-proficient readers have a connection in applying 3 types of strategies in reading. Either for survey reading strategies such as global reading strategies, problem reading strategies, or support reading strategies. Proficient readers are dominant in the use of global reading strategies and support reading strategies.keywords: reading, reading strategies, descriptive